Design, simulation and characterization of moly permalloy based electromagnetic sensor - Palianysamy, M.; Raman, M.; Shaiful Nizam, Mohyar; Wan Mokhzani, Wan Norhaimi; Ruhaizi, Mohd Hatta; Zaliman, Sauli, Prof. Madya (Trans Tech Publications, Switzerland., 2013)
Link to publisher's homepage at http://www.ttp.net/